Market entry of a company SaZ s.r.o. onto the Canadian Road-Rail market - Truska, Jan (2023)
The goal of this thesis is to analyze the Canadian Road-Rail vehicle market and to propose an optimal market entry mode for a Czech company SaZ s.r.o. The first chapter of the thesis focuses on introducing SaZ s.r.o. The second chapter of the thesis focuses on the legislation and regulations surrounding the Canadian Road-Rail vehicle market as well as the laws surrounding the export to Canada from Czech Republic. The third chapter focuses on the local competition and its analysis using SWOT analysis. The last chapter focuses on potential local customers as well as ways of approaching them plus finding the right product for the Canadian market from SaZ s.r.o.´s product range and ultimately proposing a potential market entry mode for the company. The key findings of the thesis are summarized in the thesis conclusion.